Transforming the development landscape : the role of the private sector - Brainard, Lael (Brookings Institution Press, 2006)
Private sector activity is crucial for development. It shapes the investment climate, mobilizes innovation and financing in areas such as global health, and can either cause or mitigate social and environmental harm. Yet so far, the international development debate has not focused on the role of the private sector. This volume-written by members of the private sector, philanthropic organizations, and academia-investigates ways to galvanize the private sector in the fight against global poverty. Using a bottom-up approach, they describe how the private sector affects growth and poverty alleviati.